Effects of protein and chloride source on goat growth and the economic influences - Miller, Hannah E.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
There is currently an increase in the goat population and consumption in the U.S. but minimal information available on feedlot goat nutrition. Dried distiller grains with solubles (DDGS) and Soybean Meal (SBM) are common protein sources included in feedlot style diets. SoyPlus, is a soybean-based product with a higher crude protein content than DDGS and a higher percentage of rumen undegradable protein than SBM. The combination of high crude protein content and high by-pass percentage is hypothesized to grant the animal better access to the protein and will result in improved growth. The objective of this project was to evaluate the impacts of different protein and acid sources on feedlot goat growth and carcass traits. Five isocaloric and isonitrogenic diets were created with a protein source of either SBM, DDGS, or SoyPlus and acid source of either Ammonium Chloride (AmCl) or SoyChlor. This resulted in dietary treatments of A)SBM with AmCl, B)DDGS with AmCl, C)SoyPlus with AmCl, D)SBM with SoyChlor, E)SoyPlus with SoyChlor. These treatments, of random design, were allocated to 75 growing meat goats (3 goats/pen; 5 pens/treatment). Goats had ad-libitum access to the pelleted feed and fresh water. Goats and feeder weights were recorded weekly from day 0 to 42. From this ADG, ADFI, and G:F were calculated and analyzed. There was no statistical difference in ADG, ADFI, or G:F (P>.05) between any of the treatments. Based on commodity feed prices from September 1, 2018 there is significant difference in feed costs per goat between DDGS and SBM (P=.001) and DDGS and SoyPlus(P=.017). Therefore, due to the difference in cost and similar growth performances there is benefits to using DDGS as a source of protein over SBM or SoyPlus when formulating feedlot goat diets.
Keywords: Fall 2018